The Bright Side and the Dark Side of Patient Empowerment : Co-creation and Co-destruction of Value in the Healthcare Environment - Palumbo, Rocco (Springer International Publishing : Imprint: Springer, 2017)
Patient empowerment as a key component in the future of healthcare systems is the focus of this concise in-depth analysis. It begins by defining patient empowerment as a collaborative partnership linking patients, providers, and systems, and examines the roles of health literacy, provider-patient and system-patient communication, and patient-centered care in the empowerment process. Models of positive and negative empowerment identify optimum conditions when patient and provider participate in service design and delivery as well as pitfalls and risks to patient and system when goals and input are mismatched. The book also translates concepts into practice with guidelines for empowerment strategies at the provider and organization levels to improve patient outcomes and system sustainability. Included in the coverage: Empowering healthcare organizations to empower patients - A re-design of the patient-provider partnership - Patient empowerment: a requisite for sustainability - The risks of value co-destruction in service systems - The need for enlightening and managing the dark side of patient empowerment - Disentangling the relationship between individual health literacy and patient empowerment. Straightforwardly written as a call for proactive change, The Bright Side and the Dark Side of Patient Empowerment is an illuminating text for scholars interested in patient empowerment and patient engagement, policymakers and managers operating in the healthcare field, and healthcare and social care providers.
Keywords: Business.; Health care management.; Health services administration.; Health promotion.; Health administration.; elektronické knihy; electronic books